2019
DOI: 10.1038/s41418-018-0267-4
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad and the autophagosome: exploring unanswered questions of autophagy-dependent cell death

Abstract: The recent discovery of autosis as a variant of autophagy-dependent cell death has challenged the conventional understanding of cell death and programmed cell death in cellular decision making. In contrast to previous accounts of distinct cell death modalities, autosis occurs with high autophagic activity, in the absence of apoptotic and necrotic markers and yet is not fully regulated by typical autophagy markers. Given the metabolic importance of autophagic responses and the extensive cross-talk with both apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 108 publications
(136 reference statements)
0
62
0
2
Order By: Relevance
“…However, the role of autophagy in cancer treatment is still controversial. On the one hand, autophagy may promote cell death (Denton and Kumar, 2018;Kriel and Loos, 2019); on the other hand, autophagy may play a supporting role in the malignant progression and drug resistance of tumors (Li et al, 2017;Mowers et al, 2017). In this study, we demonstrated that Eth can induce autophagosome biosynthesis, manifested by increased autophagosome formation, LC3-II conversion, and LC3B-puncta (Figures 2A-C).…”
Section: Discussionmentioning
confidence: 53%
“…However, the role of autophagy in cancer treatment is still controversial. On the one hand, autophagy may promote cell death (Denton and Kumar, 2018;Kriel and Loos, 2019); on the other hand, autophagy may play a supporting role in the malignant progression and drug resistance of tumors (Li et al, 2017;Mowers et al, 2017). In this study, we demonstrated that Eth can induce autophagosome biosynthesis, manifested by increased autophagosome formation, LC3-II conversion, and LC3B-puncta (Figures 2A-C).…”
Section: Discussionmentioning
confidence: 53%
“…The low vascularization of the theca during most of the follicular regression (Miranda et al, ) may justify the induction of autophagy to maintain cell homeostasis through clearance and selective removal of protein aggregates and dysfunctional organelles (Ryter, Cloonan, & Choi, ; Sever & Demir, ). However, under prolonged metabolic stress, autophagy may contribute to the provision of energy for apoptotic execution (Chiarelli, Agnello, Bosco, & Roccheri, ; Kriel & Loos, ). In support of this hypothesis, we observed follicular cells with highly electron‐lucid cytoplasm and a shortage of organelles under the electron microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a lysosomal degradation process. This selfdigestion process was initially considered as a cell death mechanism (type II programmed cell death) and indeed excessive autophagy triggers a specific form of cell death, termed autosis (reviewed by Kriel and Loos in this issue [21]). The molecular and functional interaction between autophagy and apoptosis has been demonstrated, as reviewed by Denton and Kumar in this issue [22].…”
Section: Mechanism Of Autophagymentioning
confidence: 99%